Transfer price confusion? - Proposing a comprehensive taxonomy for academia and practitioners - Arne Schulke; Hans Olaf Warning (Books on Demand (BoD), 2023)
Transfer prices (TP) are charged for products or services exchanged between units within a decentralized organization. A vast body of literature from three very different academic disciplines (legal, management and economics) is concerned with the topic of Transfer Pricing. Their perspectives as well as terminology differ and are sometimes not aligned. To abate this, the article proposes a unified taxonomy on Transfer Prices that distinguishes three very distinct characteristics of any TP: its Determination Method (consisting of both its Calculation Method and its Price Method), and the Determination Process by which the TP is installed. The aim of this is to guide future academic research and provide academics and business practitioners alike with precise language and logical structure for the design of Transfer Pricing Systems.
Keywords: 650; Transfer pricing; classification; scientific method; Verrechnungspreis; Klassifikation; Wissenschaftliche Methode